Determinants of Performance in Indonesian Banking: A Cross-Sectional And Dynamic Panel Analysis - Zandi Pour Joopari, GholamReza; Sarita, Buyung; Shahabi, Alireza (2012)
This paper takes into consideration the determinants of bank performance in Indonesian banking sector. It is pooled cross-sectional time series and dynamic panel data models. This research is about frameworks incorporating the traditional Structure-Conduct-Performance (SCP) and Relative Efficiency (RE) hypothesis. The estimation results show bank performance industry is competitive in a way that represents nearly a perfectly competitive market structure in Indonesian banking sector. However, no evidence turns up in the finding for the support of both the traditional SCP and RE paradigm. The negative relationship between loans to group businesses and bank performance, which is likely due to the high loans provided to group businesses, thus supporting the moral hazard hypothesis.